Ponciri Fructus Immaturus ethanol extract attenuates septic shock through inhibition of the STAT1 signaling pathway - Hwang, Yo Sep; Jang, Jun-Pil; Park, Seong-Hoon; Kim, Aeyung; Jang, Jae-Hyuk; Yoon, Hyang Ran; Yoon, Suk Ran; Park, Jun Hong; Cho, Hee Jun; Lee, Hee Gu (Frontiers in Nutrition, 2022)
Sepsis is a systemic inflammatory disease to infections and results in tissue damage and multiple organ failure. Ponciri Fructus Immaturus (PFI) is widely used in traditional medicine for allergic inflammation and gastrointestinal disorders. However, the effect of PFI on sepsis is still unknown. This study investigated the anti-inflammatory and antiseptic effects of PFI ethanol extract (PFIE) in LPS-stimulated J774 macrophages and mice with CLP- or LPS-induced sepsis, respectively. PFIE attenuates the LPS-induced production of the proinflammatory mediator NO by inhibiting the expression of iNOS in J774 cells. Real-time RT-PCR data and ELISA showed that the mRNA and protein levels of TNF-α, IL-1β, and IL-6 increased in LPS-stimulated J774 cells. However, this induction was significantly suppressed in PFIE pre-treated J774 cells. We also found that PFIE administration increased the survival rate of mice with LPS- and CLP-induced sepsis. Decreased serum levels of AST, ALT, and CK were observed after administration of PFIE, which was associated with reduced production of proinflammatory factors, such as NO, TNF-α, IL-1β, and IL-6. Moreover, PFIE suppressed the phosphorylation and nuclear translocation of STAT1 in LPS-stimulated J774 cells, suggesting that PFIE can inhibit LPS- and CLP-induced septic shock by suppressing the STAT1 activation. These findings provide the potential therapeutic relevance of PFIE in treating acute inflammatory disease.